PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 1 TULANG BAWANG TENGAH - Hazairin Habe (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2018)
Problems on this study is whether the motivation and discipline of work affect the performance of teachers on Sekolah Menengah Kejuruan (SMK) Negeri 1 Tulang Bawang Tengah. This study aims to determine the effect of motivation and discipline on teacher performance. The hypothesis formulated is no influence of motivation and discipline the performance of teachers either partially or simultaneously. The sample used in this study amounted to 69 employees. Data collection techniques by observation, questionnaire, and documentation. Methods of analysis with a quantitative approach with the help of SPSS 18.0 statistical tool for the calculation of the regression model. Partial results of hypothesis testing proves that the motivation effect on morale, as well as work discipline positive effect on teacher performance. Simultaneous hypothesis test variables and variables motivation discipline positive effect on teacher performance.